2018
DOI: 10.12659/msm.911175
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Is the Most Effective Catechin Against Antioxidant Stress via Hydrogen Peroxide and Radical Scavenging Activity

Abstract: BackgroundHydrogen peroxide-induced neuronal oxidative stress is a serious threat to the nervous system. Catechins and related compounds are effective radical scavengers that protect against nerve cell damage.Material/MethodsHere, we investigated the antioxidant property of various catechins in protecting against hydrogen peroxide, as well as their radical-scavenging activity.ResultWe found that catechins treatment effectively protected HT22 cells against H2O2-induced cell viability by decreasing and attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 46 publications
8
61
0
Order By: Relevance
“…In fact, tea catechins were broadly investigated for their antioxidant properties, and several studies defined the structural variants responsible for this activity [54]. Catechins reactivity in cell-free systems is attributable to the catechol/pyrogalloyl function on the B-ring, and their antiradical efficacy is greatly increased by esterification with a residue of gallic acid [55,56]. Indeed, large discrepancies are found in the literature among different green teas, suggesting that technological processes such as wilting, twisting, or drying, mostly affect the antioxidant properties of the product that reaches the consumer [57].…”
Section: Estimation Of Radical Scavenging Antioxidant and Antilipopmentioning
confidence: 99%
“…In fact, tea catechins were broadly investigated for their antioxidant properties, and several studies defined the structural variants responsible for this activity [54]. Catechins reactivity in cell-free systems is attributable to the catechol/pyrogalloyl function on the B-ring, and their antiradical efficacy is greatly increased by esterification with a residue of gallic acid [55,56]. Indeed, large discrepancies are found in the literature among different green teas, suggesting that technological processes such as wilting, twisting, or drying, mostly affect the antioxidant properties of the product that reaches the consumer [57].…”
Section: Estimation Of Radical Scavenging Antioxidant and Antilipopmentioning
confidence: 99%
“…The anti-oxidative effect is further augmented by the presence of the trihydroxyl structure. Further, EGCG may ameliorate lipid infusion-mediated insulin tolerance, which is related to the enhanced expression of antioxidant enzymes, such as SOD and GPx by EGCG in vivo [100]. When treating human mammary epithelial cells with EGCG, the increased expression of HMOX-1 and SOD was recorded.…”
Section: Antioxidant Compounds As Complementary Therapy In Msmentioning
confidence: 99%
“…Green tea has a high antioxidant capacity, due to the high levels of catechins present [ 64 ]. He and collaborators compared the antioxidant activities of catechins and reported that epigallocatechin gallate has greater antioxidant activity via radical scavenging activity (400 μ M) with values of 77.2 ± 4.3%, 90.2 ± 3.1%, and 100 ± 3.1% compared to its epimer, gallocatechin gallate, with values of 68.2 ± 3.4%, 82.2 ± 3.8%, and 95.5 ± 3.9% in the DPPH, ABTS, and ferric reducing antioxidant power (FRAP), respectively [ 65 ].…”
Section: Occurrence and Antioxidant Properties Of Anticoronavirus mentioning
confidence: 99%